Teosofi al-Suhrawardi al-Maqtul dan Mahzab Iluminasionisme dalam Filsafat Islam - Khairul Amin (Program studi Keagamaan Islam, 2021)
Islamic mysticism (Sufism) developed rapidly systematically (theosophy) and widely after the birth of speculative theology ('ilm al-kalām). The development is considered to have reached its peak in the hands of Syihab Al-Din Suhrawardi Al-Maqtul (d. 1191 AD) and Muhy Al-Din Ibn 'Arabi (d. 1240 AD). These two Sufi-philosophers that gave a new color that had a different nuance from the muhadditsun, mutakallimun, philosophers, and also a number of Sufis who were strongly tied to text traditions. Although both of them also have a basis of text, their interpretation is so broad, they also have different nuances. Especially the first name has a unique journey in his career, thought and life. Suhrawardi is proposing criticism as well as trying to create a synthesis as a form of criticism and renewal of thoughts that developed before his time. Inspired by the concept of light from the Koran and Al-Ghazalī's Misykat, he tried to connect what he encountered with ancient knowledge while exploring new knowledge, especially regarding the concepts and systems of light, resulting in his new theosophy called Philosophy of Isyraq. This paper will discuss the profile, context, and thoughts of Suhrawardi, especially regarding his Divine Philosophy idea which is based on light.